Readmission Events Among Patients Who Received ACT Services as Pillar I of SIRUKOGALAR at Mutiara Sukma Mental Hospital - Lindawati Lindawati; Fauzi Tsanifiandi; ACT Team ACT Team (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2022)
Readmission can occur in all diseases, including in patients with mental disorders where the sufferer experiences problems in the ability to judge reality or which one bad. One of the factors that cause recurrence in patients with mental disorders high emotional level. Another factor is the ability of patients to distinguish between family and hospital staff. In this case, most mental patients are more afraid of hospital staff than their families, so that when patients are allowed to go home the patient no longer follows directions from the family and feels that there is nothing to be afraid of. This caused the patient become not routinely monitored, and prone to experience a relapse. As the first pillar of